Lithology and porosity heterogeneity prediction using multiple seismic attributes on 3-d surveys: an example from Edim oil field, Niger delta - Alao, Peter Ayomide; Olabode, Solomon; Nwoke, Ernest Chibugo; Ata, Abubakar (International Journal of Advanced Geosciences, 2014)
This research work presents the result of integrating three-dimensional (3-D) seismic attributes and log data to determine rock property (porosity and lithology) distribution of cretaceous-aged sandstones from Edim field, in the Niger Delta. The rocks are composed of thick sandstones which are resolvable in the seismic sections and possessing good petrophysical attributes for consideration as economic reservoirs. The method used was to invert the seismic data to elastic rock properties and then interpret these rock properties in terms of reservoir properties. Three seismic attributes which are considered important in exploration for fault-related reservoirs was employed. This study explores the stratigraphy and structure of the reservoir using 3-D seismic data and multiple seismic attributes to predict porosity and the net-to-gross. By predicting porosity and lithology using seismic attributes, lateral distributions of porosity that can be used to guide development and exploration drilling for optimal hydrocarbon recovery were obtained. The sites of highest porosity and net-to-gross were found to be along and within the fault zones. This study has indicated a close relationship between faulting and reservoir development by examining relationships using 3-D seismic data. Methods and results presented in this study can be used to explore and develop fault-related reservoirs in the Niger Delta and other similar geologic settings. Keywords: Porosity, lithology, net-to-gross, predict, seismic attribute, Niger delta.